Evaluation and selection of shoe wear and orthoses for the runner - Yamashita, M. H. (Physical Medicine & Rehabilitation Clinics of North America, 2005)
Many patients have been fit with orthoses and arrive to the clinic stating that their symptoms failed to resolve, or were even worse with use of the devices. Upon further questioning, they reveal that they may or may not have been evaluated thoroughly, according to the areas of evaluation that were explored in this article. Furthermore, they may have been casted in weight bearing, and often by a technician, instead of the medical provider. They usually have no awareness of having been maintained in a neutral STJ position for casting and generally remark that they were not educated at all regarding the contributory factors for their particular gait pathomechanics or pathology. Providers who dispense custom foot orthoses include physicians, physical therapists, podiatrists, pedorthotists, and chiropractors. Because of the number of disciplines that consider foot orthoses as part of their scope of practice, the presence of a frustrating lack of uniformity with respect to knowledge base, evaluation skills, casting skills, and treatment philosophy within this population is understandable. Even the language that is used to describe positions, motions, deformity, and pathology vary based on specialty and specific training. Not surprisingly, unacceptable disparities are present, even within the same disciplines. This huge variability undermines the credibility of those practitioners who thoughtfully and deliberately fabricate devices based on sound biomechanical principles. It behooves the referring provider, as well as his/her patients, to know the background of, and the evaluation procedures that are used by, the practitioner who will be evaluating the patient for custom foot orthoses.